Treatment of rheumatoid arthritis with baricitinib or upadacitinib is associated with reduced scaffold protein NEDD9 levels in CD4+ T cells - Viktoria Golumba‐Nagy; Shuaifeng Yan; Eva Steinbach‐Knödgen; Jan Thiele; Ruth L. Esser; Thomas H. Haak; Anastasia Nikiforov; Anja Meyer; Tamina Seeger‐Nukpezah; David M. Kofler (Physiological Reports, 2023)
Abstract The JAK/STAT pathway plays a crucial role in the pathogenesis of rheumatoid arthritis (RA) and JAK inhibitors have emerged as a new group of effective drugs for RA treatment. Recently, high STAT3 levels have been associated with the upregulation of the scaffold protein NEDD9, which is a regulator of T‐cell trafficking and promotes collagen‐induced arthritis (CIA). In this study, we aimed to reveal how treatment with JAK inhibitors affects NEDD9 in CD4+ T cells from RA patients. We analyzed NEDD9 expression in CD4+ T cells from 50 patients treated with either baricitinib, tofacitinib, or upadacitinib and performed cell migration assays to assess the potential influence of JAK inhibitor treatment on CD4+ T‐cell migration. We observed that treatment with baricitinib and upadacitinib is associated with reduced NEDD9 expression in CD4+ T cells. In contrast, NEDD9 levels were not altered during treatment with tofacitinib. Moreover, treatment with baricitinib was associated with a significantly reduced migratory capacity of effector CD4+ T cells but not with impaired migration of Treg cells. This study reveals previously unknown associations between JAK inhibitor treatment and NEDD9 expression and indicates that JAK inhibitors could reduce effector T‐cell migration.